Altered plasma lipidome profile of dairy cows with fatty liver disease. (February 2017) - Gerspach, C.; Imhasly, S.; Gubler, M.; Naegeli, H.; Ruetten, M.; Laczko, E.
Abstract: Fatty liver disease is a common health problem of dairy cows occurring during the transition from pregnancy to lactation. It is a direct response to fat mobilization due to negative energy balance. Accumulation of lipids in the liver occurs if the uptake of non-esterified fatty acids by the liver exceeds the capacity of lipid oxidation or secretion by the liver. Currently, the diagnosis of fatty liver disease requires confirmation through biopsies to determine the hepatic lipid content. In view of this lack of a practical diagnostic tool, we compared the plasma lipidome of diseased dairy cows using liquid chromatography coupled to quadrupole time-of-flight mass spectrometry. Multivariate data analysis yielded 20 m / z values that were able to distinguish between dairy cows with no hepatic lipidosis and those exhibiting different stages of the disease. Based on the chromatography retention time and m / z ratios, we identified phosphatidylcholines with reduced plasma abundances in cows with fatty liver disease. The abundances of different bile acids tended to be increased. In addition, we detected two metabolites related to inflammation, resolvin E1 and palmitoyl-ethanolamine (PEA), which need to be further investigated in cattle. These results indicate that the measurement of specific representatives of phosphatidylcholines in plasma may provide a novel diagnostic biomarker of fatty liver disease in dairy cows. Highlights: The plasma lipidome was analysed by nanoUPLC coupled to a qTOF type mass spectrometer. 1491 features were matched with known lipids included in the data base built by LipidMaps. With increasing severity of fatty liver we detected decreased abundance of lipids related to phophatidylcholine metabolism.